Novel configuration for a multistage flash-mixer desalination system - Mussati, Sergio Fabian (2003)
In this paper a systematic procedure for the synthesis and design of multistage flash-mixer desalination processes is presented. The process configuration, geometric design, and optimal operating conditions are determined by minimizing the total annualized cost for a given water production. Different possible arrangements for the desaltor are embedded in a superstructure. The multistage flash-mixer system is rigorously modeled considering the most important aspects of the real process. The resolution procedure involves two phases. First, a simplified model is solved in a preprocessing phase providing the initial values and bounds, and then from these values the rigorous model is easily solved. For the simplified model resolution in the preprocessing phase, there is no need for supplying and tuning external parameters for initialization. The preprocessing phase increases the robustness of the optimization algorithm. A new configuration of the multistage flash-mixer system system resulted. This new structure differs from the conventional one because it considers distillate extraction and a new allocation of the blowdown brine (generally placed at the last stage). Different study cases are presented to illustrate the methodology robustness and computational performance.